Formation of a Summation Formula Enmeshed with Hypergeometric Function (Global Journal of Science Frontier Research, 2012)
The main aim of the present paper is to form a summation formula attached with contiguous relation and recurrence relation.
Keywords: Gaussian Hypergeometric function; Contiguous function; Recurrence relation; Bailey summation theorem and Legendre duplication formula